Factors Influencing Key Audit Matters Reporting in Thailand - Suttipun, Muttanachai (Asian Journal of Accounting Perspectives, 2020)
Research aim: This study investigated the level of Key Audit Matters (KAM) reporting in the annual reports of companies listed on the Stock Exchange of Thailand (SET) from 2016 to 2018, and examined the factors influencing KAM reporting. Design/ Methodology/ Approach: Using annual reports from 2016 to 2018, 450 annual reports of 150 companies from the SET were sampled. Content analysis by word count and checklist was used to quantify the KAM reporting, while descriptive analysis, independent sample t-test, and multiple regression were used to analyse the data. Research finding: The KAM reporting was 756.686 average words within 1.958 issues in corporate annual reports during the study period. There were significantly different levels of KAM reporting between SET100 and Non-SET100 companies as well as between audit rotation and non-audit rotation. Moreover, there was a significant positive influence of firm size and complexity on the level of KAM reporting, while profitability had a negative influence on the level of KAM reporting. Theoretical contribution/ Originality: As the first longitudinal study of KAM reporting in Thailand, the study sheds light on the factors influencing mandatory KAM reporting. Practitioner/ Policy implication: Investors can approach decision-making from the corporate characteristics affecting KAM reporting. Limitation/ Implication: External audit characters are not included when considering the influence on KAM reporting. Type of article: Research paper Keywords: KAM reporting, Annual reports, Thailand Stock Exchange JEL Classification: M40, M42